Pengaruh Gaya Kepemimpinan Transformasional Dan Budaya Organisasi Terhadap Perilaku Kerja Inovatif - Diana Yuli Nur Cahyani; Imronudin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of transformational leadership style and organizational culture on innovative work behavior.. The research sample consisted of 94 respondents selected using the Slovin method and purposive sampling technique based on a minimum work tenure of one year. Primary data were collected through a Likert-scale questionnaire and analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results indicate that transformational leadership positively and significantly influences innovative work behavior, demonstrating that leaders who inspire and drive change contribute to increased employee creativity. Furthermore, organizational culture also has a positive and significant effect on innovative work behavior, confirming that a supportive and change-oriented work environment fosters innovation. This study implies that hospital management should strengthen transformational leadership and cultivate an organizational culture that encourages innovation to enhance employee performance.